2023
DOI: 10.1039/d3nr02081a
|View full text |Cite
|
Sign up to set email alerts
|

Light-gated specific oxidase-like activity of a self-assembled Pt(ii) nanozyme for environmental remediation

Rohit Kapila,
Bhaskar Sen,
Alisha Kamra
et al.

Abstract: Artificial enzyme equivalents, also known as nanozymes, offer a practical tool for environmental remediation than their natural counterparts due to high operational stability, efficiency, and cost-effectiveness. Specific oxidase mimicking nanozymes...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…This observation clearly suggests the formation of a catalyst–substrate intermediate in a pre-equilibrium stage. , It was observed that the formation of phenoxazinone was significantly lowered when the enzymatic reaction was carried out under the N 2 environment as compared to the O 2 environment, suggesting the involvement of molecular oxygen in the reaction (Figure S19). To understand the fate of O 2 , oxidase-like behavior for Co-EA was investigated, as molecular oxygen is being reduced to water by the oxidase enzyme similar to the multicopper oxidase . The oxidase-like behavior of Co-EA was examined by monitoring the oxidation of a chromogenic substrate, 3,3′,5,5′-tetramethylbenzidine (TMB) (Figure S20A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation clearly suggests the formation of a catalyst–substrate intermediate in a pre-equilibrium stage. , It was observed that the formation of phenoxazinone was significantly lowered when the enzymatic reaction was carried out under the N 2 environment as compared to the O 2 environment, suggesting the involvement of molecular oxygen in the reaction (Figure S19). To understand the fate of O 2 , oxidase-like behavior for Co-EA was investigated, as molecular oxygen is being reduced to water by the oxidase enzyme similar to the multicopper oxidase . The oxidase-like behavior of Co-EA was examined by monitoring the oxidation of a chromogenic substrate, 3,3′,5,5′-tetramethylbenzidine (TMB) (Figure S20A).…”
Section: Resultsmentioning
confidence: 99%
“…To understand the fate of O 2 , oxidase-like behavior for Co-EA was investigated, as molecular oxygen is being reduced to water by the oxidase enzyme similar to the multicopper oxidase. 63 The oxidase-like behavior of Co-EA was examined by monitoring the oxidation of a chromogenic substrate, 3,3′,5,5′-tetramethylbenzidine (TMB) (Figure S20A). The color of the solution turned blue after the addition of Co-EA to the solution containing TMB reflecting the oxidase-like activity of Co-EA.…”
Section: Plausible Catalytic Mechanism For the Oxidation Of Oaph To P...mentioning
confidence: 99%
“…225–227 Recently, a lot of nanozyme catalytic systems have been developed to degrade phenolic pollutants. 107,109–111,117–119,121,124,228–239…”
Section: Degradation Of Environmental Pollutants Based On Nanozyme Ca...mentioning
confidence: 99%
“…[4][5][6][7][8][9] Manganese-based nanozymes are attractive owing to their multivalency nature-endowed redox behavior and multienzyme activity, 10,11 allowing for their extensive applications across a range of biomedical fields. [12][13][14][15][16] The excellent catalytic properties of manganese oxide-based nanoparticles, mainly Mn 3 O 4 and Mn 2 O 3 , have been largely attributed to the manganese-catalyzed generation of reactive oxygen species (ROS) from molecular oxygen. The highly active ROS can oxidize substrates like TMB.…”
mentioning
confidence: 99%